ANALISIS EFEKTIFITAS PENERIMAAN PAJAK HOTEL, PAJAK REKLAME DAN PAJAK PENERANGAN JALAN TERHADAP EFEKTIFITAS PENDAPATAN ASLI DAERAH PROVINSI LAMPUNG - Rifki Sudibyo; Indra Pahala (Jurnal Ilmiah Wahana Akuntansi, 2014)
This research objectives were to know Effectiveness of Hotel Tax, Advertisement Tax, and Street Lighting Tax on Effectiveness of Local Original Income (PAD). The factors that were tested in this research are Hotel Tax, Advertisement Tax, and Street Lighting Tax as independent variable, whereas Local Original Income (PAD) as dependent variable. Sample of this research are 10 Regency/ City in Lampung Province (2008-2012). This research used the secondary data and the method teqhnique of sample selection with purposive sampling. The tool of analysing data is multiple linear regression at significancy 5%. As a result of testing hypothesis partially on Advertisement Tax and Street Lighting Tax had a positive effect significant on Local Original Income (PAD). However, no evidence was found that the hotel tax has significant results, although the positive effect on Local Original Incame (PAD). Keywords : Hotel Tax, Advertisement Tax, Street Lighting Tax, Local Original Income (PAD), Local Tax, Tax Effectiveness